ANALISIS PENERAPAN HUKUM TERHADAP PELAKU TINDAK PIDANA PERJUDIAN DALAM PRAKTEK JUAL BELI CHIP GAME ON/LINEHIGGS DOMINO ISLAND (Studi Kasus Putusan Nomor 96/Pid.B/2023/PN Lbp) - Maulidya Muazzarah, Bonanda Jafatani Siregar (NERACA KEADILAN, 2023)
The online game Higgs Domino Islands is very popular among young people and adults. This online game is played simply because it is entertainment and can eliminate boredom or boredom. As time goes by, interest in playing this online game is increasing because there is a gambling content for game players. online higgs domino island is misused to make a profit by opening a business area to carry out the practice of buying and selling online chips in the game. Buying and selling online game chips is very disturbing to the public, it can cause moral and material damage. The aims of this research are: 1 To find out what are the factors in the occurrence of criminal acts of gambling in the practice of buying and selling chips for the online game Higgs Domino Island 2 To find out how judges consider in imposing criminal sanctions against perpetrators of gambling in the practice of buying and selling chips for the online game Higgs Domino Island 3 To find out Obstacles that occur by law enforcement officials in eradicating perpetrators of criminal acts of gambling in the practice of buying and selling chips for the online game Higgs Domino Island. This research method: this type of research is normative and empirical law data sources secondary, primary and tertiary legal materials Data collection using interviews and literature study data analysis techniques using qualitative data Conclusion: Factors that cause criminal acts of gambling in the practice of buying and selling online Higgs Domino Island game chips, namely economic factors, environmental factors, profit factors, lack of legal awareness, growth factors in the Higgs Domino Island game industry, lack of regulations or legal rules. The judge imposed criminal sanctions against The defendant was sentenced to 5 months in prison under Article 303 paragraph 1. The obstacles faced by law enforcement officials in eradicating criminal acts of gambling in the practice of buying and selling online game chips Higgs Domino Island are the inability to track the practice of buying and selling online game chips, limited resources, lack of goods. There is strong evidence that there is no public support or concern in eradicating gambling and law enforcers act if there are reports from the public.